God : A Biography - Miles, Jack, 1942- (1996)
What sort of "person" is God? Is it possible to approach him not as an object of religious reverence, but as the protagonist of the world's greatest book--as a character who possesses all the depths, contradictions, and abiguities of a Hamlet? In this "brilliant, audacious book" (Chicago Tribune), a former Jesuit marshalls a vast array of learning and knowledge of the Hebrew Bible to illuminate God--and man--with a sense of discovery and wonder.
Can God's life be written? -- Creator -- Destroyer -- Friend of the family -- What makes God godlike? -- Liberator -- Lawgiver -- Liege -- Conqueror -- Father -- Arbiter -- Does God fail? -- Executioner -- Holy one -- Does God love? -- Wife -- Counselor -- Guarantor -- Fiend -- Sleeper -- Bystander -- Recluse -- Puzzle -- Absence -- Ancient of days -- Scroll -- Perpetual round -- Does God lose interest? -- The Books of the Tanakh.
Includes bibliographical references (pages 413-431) and index.
Keywords: Bible. -- Criticism, interpretation, etc; God -- Biblical teaching; Bible as literature; Criticism, interpretation, etc